Bio-inspired ternary artificial nacre nanocomposites based on nanoclay/polymer matrix/graphene oxide with optimal balance of strength and toughness - Han, Jian Teng (2018)
Natural nacre has an ordered layered structure made of mainly inorganic calcium carbonate platelets highly arranged in an organic protein matrix, which exhibits high mechanical properties. This report aims to fabricate artificial nacre that can match or surpass the tensile mechanical properties of natural nacre. Binary nanocomposites such as CMC/SUM, CMC/GO – x% and CMC/RGO – x%, and ternary nanocomposites such as SUM/CMC/GO – x% and SUM/CMC/RGO – x% have been fabricated. The nanocomposite films were characterized with XRD, TGA, FESEM, UV-Vis spectrometry and tensile mechanical testing to understand the various properties associated with the nanocomposites. The structure of the nanocomposites was analyzed and compared with that of natural nacre. Further analysis into the thermal properties and transparency of the nanocomposites were conducted and discussed for different application requirements. Tensile mechanical properties of binary and ternary nanocomposites were thoroughly compared with similar work from other literature on GO-based nanocomposites. The nanocomposites fabricated in this report have shown to exhibit superior tensile mechanical properties than natural nacre. Furthermore, ternary nanocomposites exhibit synergistic enhancement in strength, stiffness and toughness. Research in nanocomposites of this kind continues to inspire studies in the creation of newer and better materials with enhanced mechanical materials for various applications such as gas and fire barrier, structural materials, functional coatings and substrates.